I wonder why my tummy rumbles : and other questions about my body - Avison, Brigid (Danbury, Connecticut : Grolier Inc, 1999)
With information and quirky facts to explain everything from 'Where do I come from?' to 'What is sleep-walking?'.
Includes index
Keywords: Encyclopedias; Questions and answers